Strategi Guru dalam Menumbuhkan Minat Baca Siswa Sekolah Dasar - Faidia Dewantara Hasibuan; Siti Quratul Ain (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
This research is based on the problems of students who have difficulty reading at the beginning. The aim of this research is to describe teachers' strategies for fostering interest in reading in grade IV students and identify what are the inhibiting factors for teachers in fostering interest in reading in grade IV students in elementary schools. Descriptive qualitative research is the method used in this research. Data collection in this research used documentation, interviews and observation. Data analysis in this research includes: Data reduction, displaying data or presenting data and drawing conclusions and then operating. The results of this research conclude that although several inhibiting factors in fostering students' interest in reading, such as strategies and approaches that will be used to increase literacy, are not well understood by teachers, schools do not implement literacy activities, insufficient reading materials and parental involvement. with schools in literacy activities, it does not have a bad impact on students because teachers continue to strive for strategies to increase students' interest in learning.